Peranan Audit Operasional dalam Meningkatkan Efektivitas dan Efisiensi Fungsi Pembelian pada PT. Organ Jaya - Djanegara, H. Moermahadi Soerja; Triandi, Triandi; Praktikno, Skundita (Jurnal Ilmiah Ranggagading (JIR), 2009)
The goal of this research is to evaluate the role of operational audit. Is it adequate to increase buying function effectiveness and efficiency ? Based on finding result obtained when operational audit was done in buying function, do the managements take steps to optimize activities that have not been optimized yet ? Based on research that has been done, several facts as follows are found. The firm has had standard procedure and policy of buying. The buying procedure and policy are always evaluated by internal auditors in a team, either the procedure and policy effectiveness themselves or the realization. The operational audit should be carried out by internal auditors. In PT Organ Jaya, operational audit is handled by internal auditors team arranged by general manager. The director assigns general manager to form internal auditors team. The realization of auditing is done in auditing phases. Operational audit in 2007 period yielded several finding results. The findings obtained are among other things as follows. The firm has never renewed suppliersâ name and has never tried to bring about tender process in buying. Storehouse department still has lack of employees, it can be observed when receiving goods in a large numbers. Store department side is unable to handle in receiving, checking, and storing of goods in storehouse. The storehouse department side often does not conduct checking on quality of goods received. Sending and receiving of goods in storehouse is often late. There are found of worn-out stocks which are not able to be produced. Keywords : Operational Audit; Buying function